Borges and the refutation of idealism: a study of "tlön, uqbar, orbis tertius" (1996)
This paper tries to demónstrate that Borges' celebrated story, "Tlón, Uqbar, Orbis Tertius," contains a reductio ad absurdum argument of a form of subjective idealísm usually associated with Berkeley. To show the íncoherences that result from the idealísm of Berkeley, Borges makes use of ideas which may be fruitfully illuminated by comparison with kantian arguments against subjective idealísm. He puts these arguments ín the form of a cuento which illustrates the absurdities and contradictions of this ídealist position. Specifically, he demónstrales that a radically subjective idealísm is self-contradictory since it renders all objective experience indetermínate and incoherent.